2014
DOI: 10.18497/iejee-green.87708
|View full text |Cite
|
Sign up to set email alerts
|

What Kind of Actions are Appropriate? Eco-School Teachers' and Instructors' Ranking of Sustainability- Promoting Actions as Content in Education for Sustainable Development (ESD)

Abstract: has provided knowledge about teachers' understanding of sustainable development, different teaching traditions and approaches, but knowledge is still lacking about teachers' views on including different sustainability-promoting actions. The aim of the article is to study Eco-School teachers ' and instructors' views

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…Furthermore, this hypothesis was verified in a study in which we found that students in ESD-certified schools do not experience more transformative teaching approaches in comparison to students in non-ESD schools (Boeve de-Pauw, Gericke, Olsson, & Berglund, 2015). There are also strong indications that teachers generally teach environmental and sustainability issues in a normative manner (Boeve-de Pauw & Van Petegem, 2011;Borg et al, 2012), including teachers in certified schools (Stagell et al, 2014). Moreover, according to Schwartz's theories described earlier, girls are expected to be more receptive to, and more tolerant of, normative teaching than boys.…”
Section: The Implication Of the Gender Gap For Esdmentioning
confidence: 58%
“…Furthermore, this hypothesis was verified in a study in which we found that students in ESD-certified schools do not experience more transformative teaching approaches in comparison to students in non-ESD schools (Boeve de-Pauw, Gericke, Olsson, & Berglund, 2015). There are also strong indications that teachers generally teach environmental and sustainability issues in a normative manner (Boeve-de Pauw & Van Petegem, 2011;Borg et al, 2012), including teachers in certified schools (Stagell et al, 2014). Moreover, according to Schwartz's theories described earlier, girls are expected to be more receptive to, and more tolerant of, normative teaching than boys.…”
Section: The Implication Of the Gender Gap For Esdmentioning
confidence: 58%
“…However, ESD teaching should be not limited to actions at the individual level or the school level but go further to collective actions [40]. Connell and colleagues in 1998 [80] but also Stagel [81], Almers, Askerlund and Apelqvist some years later, in 2014 [81], showed that students had taken more individual actions in a private sphere while collective ones required for the democratic change of social structures tend to be excluded. Thus, students' gain little experience in public sphere action [81].…”
Section: Impact Of Actionmentioning
confidence: 99%
“…It could be argued that these textbooks exhibit limitations especially with regards to fostering competence for taking democratic and political action for SD. This is interesting to note, as it has been observed elsewhere (Stagell et al 2014) that teachers sometimes find it inappropriate to discuss precisely such action in ESD. As the quotes discussed above illustrate, the observed forms of obscuring complexities and conflicts are primarily related to the ways in which the social dimension often remains underdeveloped in textbooks.…”
Section: Obscuring Conflictsmentioning
confidence: 60%